Mitochondrial Ca2+ Overload Leads to Mitochondrial Oxidative Stress and Delayed Meiotic Resumption in Mouse Oocytes - Zhang, Luyao; Wang, Zichuan; Lu, Tengfei; Meng, Lin; Luo, Yan; Fu, Xiangwei; Hou, Yunpeng (Frontiers in Cell and Developmental Biology, 2020)
Abstract Overweight or obese women seeking pregnancy is becoming increasingly common. Human maternal obesity gives rise to detrimental effects during reproduction. Emerging evidence has shown that these abnormities are likely attributed to oocyte quality. Oxidative stress induces poor oocyte conditions, but whether mitochondrial calcium homeostasis plays a key role in oocyte status remains unresolved. Here, we established a mitochondrial Ca2+ overload model in mouse oocytes. Knockdown gatekeepers of the mitochondrial Ca2+ uniporters Micu1 and Micu2 as well as the mitochondrial sodium calcium exchanger NCLX both increased mitochondrial Ca2+ concentration. The overload of mitochondria Ca2+ in oocytes impaired mitochondrial function, leaded to oxidative stress and changed Protein kinase A(PKA) signaling associated gene expression as well as delayed meiotic resumption. Using this model, we aimed to determine the mechanism of delayed meiosis caused by mitochondrial Ca2+ overload and whether oocyte-specific inhibition of mitochondrial Ca2+ influx could improve the reproductive abnormalities seen with obesity. As expected, the percentage of oocytes that successfully progressed to the germinal vesicle breakdown stage and extruded the first polar body during in vitro culture increased significantly, and the expression of PKA signaling genes and mitochondrial function recovered after appropriate mitochondrial Ca2+ regulation. Additionally, some indicators of mitochondrial performance—such as adenosine triphosphate (ATP) and reactive oxygen species (ROS) levels and mitochondrial membrane potential—recovered to normal. These results suggest that the regulation of mitochondrial Ca2+ uptake in mouse oocytes has a significant role during oocyte maturation as well as PKA signaling and that proper mitochondrial Ca2+ reductions in obese oocytes can recover mitochondrial performance and improve obesity-associated oocyte quality.